Struktur Frasa Verbal Bahasa Melayu Riau Dialek Kampar: Teori X-Bar - Ermawati. S; Hermaliza; Alber (Perspektif Pendidikan dan Keguruan, 2021)
Abstract There have been several research studies that discussed verb phrases. But only some researchers analyse the X-bar theory concerning regional languages in Riau. The author attempts to demonstrate the structure of verb phrase in the Malay dialect of Kampar by using the X-bar theory.This study aims to find and analyse the rules structuring verb phrases contained in the Malay dialect of Kampar. This research was conducted through a field observation by using the descriptive method. According to the findings of the study, it is found that the principles for creating verb phrase structures in Kampar dialect were. 1) FV ---> V+N, ŋikIʸ umpʷIɁ ‘(me)motong rumput’/ Cut the grass; 2) FV ---> V+Spes, bagoɣaɁ lo ‘memasak’/ cook; 3) FV ---> Spes+V, ola makan ‘sudah makan’/ have got the food; 4) FV ---> NEG+V+Spes, ndaɁ dataŋ do ‘tidak datang’/ did not come; 5) FV ---> V+V, paʸ makan ‘pergi makan’/ get to eat; 6) FV ---> Adj+V, paya ŋasʷoňo ‘susah mengasuhnya/menjaganya’/ its hard to take care of; and 7) FV ---> V, motoŋ ‘menoreh/menyadap karet’/ tap the rubber. Key words: Riau Malay, Kampar Dialect, Verb Phrase Structure, X-Bar Theory